2021
DOI: 10.5663/aps.v9i2.29381
|View full text |Cite
|
Sign up to set email alerts
|

How Can Urban Parks Support Urban Indigenous Peoples? Exploratory Cases from Saskatoon and Portland

Abstract: In Anglo settler states, parks and Indigenous peoples interact in myriad ways, given the tight connection between Indigenous peoples and land and that parks are manifestations of settler control of land and heritage. Current park–Indigenous research is limited by a focus on rural locales, despite that more than half of Indigenous peoples live in urban areas. This exploratory paper draws connections between literature rooted in urban Indigenous studies and park management. I argue the literature’s current empha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…While no urban Indigenous Protected and Conserved Areas have yet to be established in Canadian cities, experience with IPCAs in other geographies has shown that they fundamentally differ from state-led processes in their governance, emphasis on Indigenous knowledge and legal systems, and acceptance of sustainable customary use, such as spiritual, cultural, economic and subsistence functions (Finegan, 2021;Mansuy et al, 2023;Townsend and Roth, 2023). As noted by Hernandez and Vogt (2022), p. 38 "to Indigenize restoration [and other environmental stewardship], Indigenous peoples require a seat not just at the table but at the head of the table. "…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While no urban Indigenous Protected and Conserved Areas have yet to be established in Canadian cities, experience with IPCAs in other geographies has shown that they fundamentally differ from state-led processes in their governance, emphasis on Indigenous knowledge and legal systems, and acceptance of sustainable customary use, such as spiritual, cultural, economic and subsistence functions (Finegan, 2021;Mansuy et al, 2023;Townsend and Roth, 2023). As noted by Hernandez and Vogt (2022), p. 38 "to Indigenize restoration [and other environmental stewardship], Indigenous peoples require a seat not just at the table but at the head of the table. "…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted by the National Association of Friendships Centers (2022), the urban Indigenous context is complex, and urban Indigenous populations are not easily defined solely on demographic or geographic criteria used in government census programs. Furthermore, individuals' relationships with urban geographies are nuanced and reflect colonialism's historical and ongoing consequences, such as deterritorialization and systemic racism (Peters, 2004;Finegan, 2021). For example, Indigenous urban populations are more mobile than non-Indigenous residents.…”
Section: The Significance Of Urbanized Areas To Indigenous Peoples In...mentioning
confidence: 99%
See 3 more Smart Citations